Illocutionary Speech Acts Analysis in Nadhira Afifa's Speech Harvard University graduation as a student speaker in 2020 - AHMAD WEFI (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2022)
Abstract                The purpose of this study is to clarify the types of intraverbal acts in Nadira Affifa's speech as a student speaker  in the Master's program in public health in 2020 after graduating from Harvard University. This study focused on the types of intra-speech behavior promoted by Yule (1996). This study used qualitative explanations by analyzing Nadira's speech as the main data. In addition, the source of the data for this survey was collected by downloading audio and video  from YouTube. The data is then analyzed and converted into a document. In addition, the data was grouped into five types of spoken diplomatic behavior. The findings prove that there are four types of spoken diplomatic behavior used in Nadira's speech. They were representative, expressive, instructive, and authoritative. In this term, there is no declarative intra-speech act type. Apparently, the preferred mode of spoken diplomatic activity was typical. That semester, Nadilla provided information about the importance of being part of the public health of the day  she was worried about. In the meantime, the percentages showed the most used and  least used  types of spoken diplomatic behavior throughout Nadira's speech. They were representative (56.4%), expressive (30.7%), directive (5.1%), binding (7.7%), and declarative (0%). This means that representative and expressive ones are prioritized. This happens because the speaker giving the context and speech is the speaker of the  graduation student.